Household economy at Wall Ridge : a fourteenth-century Central Plains farmstead in the Missouri Valley - Lensink, Stephen C.; Schermer, Shirley J., 1946-; Tiffany, Joseph A., 1948- (The University of Utah Press, 2020)
"Household Economy at Wall Ridge tells the story of a Native American household that occupied a lodge on the eastern Plains border during the early 1300s AD. Contributors use cutting-edge methods and the site's unparalleled archaeological record to shed light on the daily technological, subsistence, and dietary aspects of the occupants' lives. This work represents the first comprehensive study of a prehistoric Central Plains household in over half a century"--